Evaluation of adipocytokines in obese children with insulin resistance - Taşçılar, Mehmet Emre; Çekmez, Ferhat; Meral, Cihan; Pirgon, Özgür; Tanju, İ. A. and Canpolat, Fuat Emre and Abacı, Ayhan and Tapan, Serkan and Eker, İbrahim (The Turkish Journal of Pediatrics, 2011)
Obesity and overweight are among the most serious health problems in western societies and an increasing problem in developing countries. Recent studies indicate an important role of adipose tissue hormones, or "adipokines", in obesity-associated complications. To investigate the relation of two circulating adipokines (visfatin, adiponectin) with markers of insulin sensitivity and obesity in children, 40 obese children and 40 control children were recruited. Homeostasis model assessment for insulin resistance (HOMA-IR) and visfatin levels (4.99 +/- 2.08 vs. 1.47 vs. 0.7, p < 0.001; 31.3 +/- 11.1 vs. 18.5 +/- 10.7, p < 0.001, respectively) were significantly elevated and adiponectin levels (2.01 +/- 1.02 vs. 12.5 +/- 6.2, p < 0.001) were significantly lower in the obese group. Comparisons of the clinical and metabolic characteristics between insulin-resistant and noninsulin-resistant groups in obese children are summarized. The insulin-resistant group had higher visfatin levels (36 +/- 9.7 vs. 22.9 +/- 7.6, p < 0.001) and lower adiponectin levels (1.7 +/- 1.05 vs. 2.5 +/- 0.77, p: 0.016). Visfatin was correlated positively and adiponectin was correlated negatively with body mass index standard deviation score (BMI-SDS) and HOMA-IR. The role of various adipokines as connectors between obesity and diabetes mellitus has been better elucidated in recent years. Based on the findings of this study, visfatin and adiponectin levels can be used as specific markers for insulin sensitivity.